1993
DOI: 10.1172/jci116303
|View full text |Cite
|
Sign up to set email alerts
|

Independent expression of fibril-forming collagens I, II, and III in chondrocytes of human osteoarthritic cartilage.

Abstract: Normal and osteoarthritic human articular cartilage was investigated by in situ hybridization for expression patterns of the fibrillar collagens type I, II, and III to evaluate phenotypic changes of articular chondrocytes related to the disease. In 11 out of 20 samples, a defined subset of chondrocytes in the superficial and upper middle zone of osteoarthritic cartilage showed significant levels of cytoplasmic al (III) mRNA, whereas strong signals of at (II) mRNA were found in the upper and lower middle zone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
143
4
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(167 citation statements)
references
References 38 publications
14
143
4
6
Order By: Relevance
“…Current hypotheses to explain the changes in OA chondrocytes include the notion that phenotypic alterations of the cells occur in response to changing signals or matrix composition (10)(11)(12)(13). It is well known that chondrocytes can adopt different phenotypes, including those associated with the growth plate (resting, proliferating, hypertrophic), those associated with the different zones of AC, and the dedifferentiated phenotype observed in monolayer culture (3,7,13,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current hypotheses to explain the changes in OA chondrocytes include the notion that phenotypic alterations of the cells occur in response to changing signals or matrix composition (10)(11)(12)(13). It is well known that chondrocytes can adopt different phenotypes, including those associated with the growth plate (resting, proliferating, hypertrophic), those associated with the different zones of AC, and the dedifferentiated phenotype observed in monolayer culture (3,7,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that a major change in the chondrocyte phenotype in OA involves a switch in the types of collagen molecules that are synthesized. Clusters of chondrocytes in OA cartilage have been shown to express types I and III collagens, which are not normally found or found at very low levels in normal AC (10,12,(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these chondrocytes, the expression levels of type IX and type XI procollagens as well as link protein were higher than those in the cells given a control siRNA ( Figure 3C). In dedifferentiating chondrocytes, the expression levels of type I and type III procollagens, which are not very high in normal chondrocytes, have been shown to be induced in parallel with the decline in cartilage matrix gene expression (34)(35)(36)(37)(38). Thus, we expected that the expression of those procollagen genes might be reduced by the suppression of ␣v or ␤5 integrin expression.…”
Section: Determination Of Dominant Integrins In Human Articular Chondmentioning
confidence: 98%